Expanded Diversity and Phylogeny of mer Genes Broadens Mercury Resistance Paradigms and Reveals an Origin for MerA Among Thermophilic Archaea - Christakis, Christos A.; Barkay, Tamar; Boyd, Eric S. (Frontiers in Microbiology, 2021)
Mercury (Hg) is a highly toxic element due to its high affinity for protein sulfhydryl groups, which upon binding, can destabilize protein structure and decrease enzyme activity. Prokaryotes have evolved enzymatic mechanisms to detoxify inorganic Hg and organic Hg (e.g., MeHg) through the activities of mercuric reductase (MerA) and organomercury lyase (MerB), respectively. Here, the taxonomic distribution and evolution of MerAB was examined in 84,032 archaeal and bacterial genomes, metagenome assembled genomes, and single-cell genomes. Homologs of MerA and MerB were identified in 7.8 and 2.1% percent of genomes, respectively. MerA was identified in the genomes of 10 archaeal and 28 bacterial phyla previously unknown to code for this functionality. Likewise, MerB was identified in 2 archaeal and 11 bacterial phyla previously unknown to encode this functionality. Surprisingly, homologs of MerB were identified in a number of genomes (~50% of all MerB-encoding genomes) that did not encode MerA, suggesting alternative mechanisms to detoxify Hg(II) once it is generated in the cytoplasm. Phylogenetic reconstruction of MerA place its origin in thermophilic Thermoprotei (Crenarchaeota), consistent with high levels of Hg(II) in geothermal environments, the natural habitat of this archaeal class. MerB appears to have been recruited to the mer operon relatively recently and likely among a mesophilic ancestor of Euryarchaeota and Thaumarchaeota. This is consistent with the functional dependence of MerB on MerA and the widespread distribution of mesophilic microorganisms that methylate Hg(II) at lower temperature. Collectively, these results expand the taxonomic and ecological distribution of mer-encoded functionalities, and suggest that selection for Hg(II) and MeHg detoxification is dependent not only on the availability and type of mercury compounds in the environment but also the physiological potential of the microbes who inhabit these environments. The expanded diversity and environmental distribution of MerAB identify new targets to prioritize for future research.